Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Peserta Didik tentang Norma dan Aturan Kelas V SD Inpres Oesapa Kota Kupang - Selan, Inda Tridia; Taneo, Silvester Petrus; Kota, Martha Khristina (ARZUSIN, 2025)
This study aims to improve student learning outcomes in Civics subjects through the application of the Problem Based Learning (PBL) learning model, this type of research is Classroom Action Research (PTK) which is carried out in two cycles. The research site was held at SD Inpres Oesapa Kupang City. The data collection techniques used were observation, test techniques and documentation studies. Data analysis technique is descriptive qualitative. The research subjects were fifth grade students of SD Inpres Oesapa which amounted to 27 st.udents consisting of 18 male students and 9 female students. Based on the research shows that the results in cycle I of 27 people who completed 11 people (41%), while those who did not complete 16 people (59%). However, in cycle II experienced an increase, namely Cycle II of 27 students declared complete amounted to 25 people (93%), while those who did not complete 2 people (7%). For 2 people who are not complete will be given remedial and enrichment by the homeroom teacher.